2021
DOI: 10.1155/2021/6676005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Peracetic Acid on the Dynamic Cyclic Fatigue of Heat-Treated Nickel-Titanium Rotary Endodontic Instrument

Abstract: Peracetic acid (PAA) is widely used as a sterilizing/disinfecting agent, and, in endodontics, it has been introduced as a promising irrigant in root canal treatment. It has been used at different concentrations to achieve various functions. However, endodontic instruments in contact with PAA of a certain concentration may affect their fatigue resistance. Therefore, the aim of this study was to investigate the impact of PAA on the cyclic fatigue resistance of three commercial heat-treated nickel-titanium (NiTi)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
2
0
1
Order By: Relevance
“…Al-Nasrawi ve ark. 34 ise %0,35'lik perasetik asitin OC eğesinin döngüsel yorgunluk direncini olumsuz etkilediğini bildirmiştir. Aynı çalışmada perasatik asit uygulanan OC eğelerinin kırık parça uzunlukları kontrol grubundan farklı bulunmuştur ve bu bulgu bizim çalışmamız ile paraleldir.…”
Section: Endodontik İrrigasyon Solüsyonlarının One Curve Eğesinin Dö...unclassified
“…Al-Nasrawi ve ark. 34 ise %0,35'lik perasetik asitin OC eğesinin döngüsel yorgunluk direncini olumsuz etkilediğini bildirmiştir. Aynı çalışmada perasatik asit uygulanan OC eğelerinin kırık parça uzunlukları kontrol grubundan farklı bulunmuştur ve bu bulgu bizim çalışmamız ile paraleldir.…”
Section: Endodontik İrrigasyon Solüsyonlarının One Curve Eğesinin Dö...unclassified
“…The study's lack of other irrigation solutions can be highlighted as its major limitation. 5 It has also been reported that increased NaOCl concentration affects the hardness of structural dentin and may lead to the dentinal crack formation during RCT. 7 Therefore, selecting an appropriate irrigation solution concentration must be taken into account to avert failure during the RCT.…”
mentioning
confidence: 99%
“…Besides, the risk of apical extrusion can be avoided by using a negative pressure irrigation system (e.g., EndoVac). 4 , 5 , 6 …”
mentioning
confidence: 99%